Personagens negras infantis: retalhos de histórias - Silva, Ayodele Floriano (Universidade Federal de São Carlos, 2022)
The present work aims to analyze and interpret the experiences of black children's characters from contemporary children's literature books present in the collection of Literatura Infantil Negra e a Primeira Infância project. Therefore, I mobilized the following concepts from Literary Theory and the field of Children's Literature: literature, central character, space, time, children's literature and narrative. In addition, I recovered some of the debates present in studies on ethnic-racial relations in children's and youth literature in Brazil. As a methodological procedure, I started with a bibliographical research consisting of four forms of reading: exploratory reading and selective reading of the collection, analytical reading and interpretive reading of selected books. In the third and fourth reading, the following books were analyzed and interpreted: Cheirinho de neném (SANTANA, 2011), Quero ser do meu tamanho (SÁTIRO, 2011), Alice vê (ROSA, 2013), O cabelo de Cora (CÂMARA, 2013), O mundo no black power de Tayó (OLIVEIRA, 2013), Iori descobre o sol – O sol descobre Iori (FAUSTINO, 2015), Amoras (EMICIDA, 2018), Bucala: a pequena princesa do quilombo de Cabula (NUNES, 2019), E foi assim que eu e a escuridão ficamos amigas (EMICIDA, 2020) e Meia Curta (FÉLIX, 2020). The central experiences of the black children's characters found were: fear of the dark, change of preference; becoming a big sister, body perception, racial discrimination and blackness. These experiences are both objective and subjective, taking place in a spatial (home, school, street, park and nature) and temporal (chronos, kairós and aión) multiplicity; and involve interactions with family members, other child characters, nature beings, mythical and imaginary beings.In the end, it was possible to conclude that these experiences showed two patterns.The first involves a set of experiences that can be experienced by children's characters from different ethnic-racial backgrounds, for example, fear of the dark. The second pattern is related to experiences linked to racism, which directly affected black children's characters, and to blackness, as a confrontation with this form of violence with the appreciation of black aesthetics and culture.
Children's black characters: scraps of stories
Keywords: Literatura infantil; Personagens negras; Experiências; Children's literature; Black characters; Experiences; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO